Handbook of political violence and children: psychosocial effects, intervention, and prevention policy - Greenbaum, Charles W.; Yahia, Mohammed Haj; Hamilton, Carolyn (Development at risk series, 2021)
Foreword / by Michael Wessells -- Introduction: Integration of knowledge on children and political violence / Charles W. Greenbaum, Muhammad M. Haj-Yahia, and Carolyn Hamilton -- Developmental aspects of political violence : attachment theoretical approach / Raija-Leena Punamaki -- Growing up with fear : the impact of terrorism and political violence on the development of children / James Garbarino, Amy Governale, and Danielle Nesi -- A systematic review of the socio-economic effects of exposure to political conflict / Sami H. Miaari and Amit Loewenthal -- Ethical and methodological considerations for researching children exposed to political violence / Cyril Bennouna and Lindsay Stark -- Effects of political violence exposure on the family and parenting environment : the case of Palestinians and Israelis / Eric F. Dubow, Lynnel C. Goodman, Paul Boxer, Erika Y. Niwa, L. Rowell Huesmann, Simha Landau, Shira Dvir Gvirsman, Khalil Shikaki, and Cathy Smith -- The relationship between the exposure of Palestinian adolescents to cumulative political violence and the development of post-traumatic stress symptoms : a study of the moderating effects of age, gender, and parenting styles / Muhammad M. Haj-Yahia and Charles W. Greenbaum -- Paying attention to the children : the intergenerational transmission of father's traumatic wartime captivity / Zahava Solomon, Gadi Zerach, and Alana Siegel -- The development of moral thinking in youth exposed to war-related violence / Cecilia Wainryb -- Children born of war in northern Uganda : stigma, marginalization, and resistance / Myriam Denov -- "My heart feels chained" : the effects of economic precarity on syrian refugee parents living in Lebanon / Bree Akesson and Dena Badawi -- Self-regulation capacities in children exposed to trauma and political violence / Sophie Brickman, Meir Fox, and Ruth Pat-Horenczyk -- Teachers as agents of clinical practice during armed conflict / Michelle Slone, Yael Mayer, and Ayelet Gilady -- Empowering culturally diverse populations affected by violence : realizing the promise of strengthening family interventions / Jordan Farrar and Theresa Betancourt -- Promoting resilience in children exposed to war and political violence by strengthening parenting / Abigail Gewirtz, Hayley Anne Rahl-Brigman, and Kate Senich -- Therapeutic interventions with Israeli children exposed to continuous traumatic stress of political violence / Tamar Lavi -- Children not soldiers : preventing the recruitment and use of children by armed forces and groups / Francesca Capone -- The role of the International Criminal Court in the prevention of exposure of children to political violence / Gloria-Atiba Davies -- Transitional justice and children : prioritizing child protection and education reform / Cecile Aptel, Saudamini Siegrist, and Friedrich Affolter -- Gendering security : the role of young women and girls in terrorism and (countering) violent extremism / Elizabeth Yarrow -- Conclusion: Research, intervention, and prevention of children's exposure to political violence : the role of the social sciences and international law / Charles W. Greenbaum, Muhammad M. HajYahia, and Carolyn Hamilton.